Honestly, why are you donating money to charity? An experimental study about self-awareness in status- seeking behavior - Mitesh Kataria; Tobias Regner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
This study investigates experimentally whether people in retrospective are self-aware that they engage in status-seeking behavior. Subjects participated in a real-effort task where effort translated into a donation to a charity. Within-subjects we varied the visibility of their performance (private/public feedback). On average subjects exerted more effort in the public treatment. After the real effort task subjects were asked to state their retrospective beliefs about their performance in public given feedback about their performance in private, and about the performance of other subjects in public given the average performance in private. Between-subjects we varied the compensation (low/high) for accurate estimates. Our results show a lack of self-awareness about status-seeking behavior that is robust to increased belief compensation. We also found that subjects expected others to be as status-seeking as they are themselves or even less.
Keywords: C91; D03; D84; 330; Social status; self-image; self-awareness; self-deception; experiment; beliefs; Spende; Persönlichkeitspsychologie; Sozialer Status; Test